Faecal alpha 1 antitrypsin as a marker of gastrointestinal disease in HIV antibody positive individuals. Issue 2 (February 1996) - Sharpstone, D; Rowbottom, A; Nelson, M; Gazzard, B
Abstract : Hypoalbuminaemia and diarrhoea are common complications of HIV infection and substantial causes of morbidity, but the specific intestinal pathologies that cause enteric protein loss have not been clearly defined. Two hundred and twenty stool samples from patients with a variety of HIV related conditions were analysed for faecal alpha 1 antitrypsin. Patients with intestinal Kaposi's sarcoma had a significantly raised faecal alpha 1 antitrypsin value and hypoalbuminaemia. A faecal alpha 1 antitrypsin value of greater than 0.3 mg/g wet stool has a sensitivity of 94% and a specificity of 76% for the diagnosis of intestinal Kaposi's sarcoma in HIV positive individuals. Patients with cytomegalovirus and bacterial enteritis had raised faecal alpha 1 antitrypsin values but levels were normal for all other intestinal pathologies compared with pathogen negative stool. The combination of faecal alpha 1 antitrypsin concentration greater than 0.2 mg/g, a negative stool culture for enteric bacteria, and the absence of palatal Kaposi's sarcoma has a sensitivity of 55% and specificity of 88% for the diagnosis of enteric cytomegalovirus infection.